Sustainable Immunomodulatory via Macrophage P2Y12 Inhibition Mediated Bioactive Patche for Peritendinous Antiadhesion - Zaijin Tao; Shuo Wang; Jingwen Liu; Tonghe Zhu; Jia Jiang; Shen Liu; Xin Ma (Advanced Science)
Abstract Persistent anti‐inflammatory responses are critical for the prevention of peritendinous adhesion. Although modified anti‐adhesion barriers have been studied extensively, the immune response induced by the implants and the unclear mechanism limits their application. In this research, the advantage of the multi‐functionalities of CA (caffeic acid) is taken to synthesize biodegradable poly (ester urethane) urea elastomers with ester‐ and carbamate‐bonded CA (PEUU‐CA). PEUU‐CA is electrospun into bioactive patches that can uniquely present a sustained CA niche, referred to as BPSN. In the early stage of degradation, the breakage of the ester bond from BPSN is the dominant factor contributing to the early release of CA. In the later stage of BPSN degradation, the breakage of the ester and carbamate bonds contributes to the sustained release of CA. In vitro experiments showed that CA, when specifically bound to the P2Y12 receptor, down‐regulated the expression and function of active P2Y12, effectively inhibiting the aberrant activation of macrophages and the secretion of inflammatory chemokines. BPSN addresses the foreign body reaction induced by macrophage‐dominated biomaterial implantation and the issue of the short‐term release of drugs at later stages of adhesion, providing a feasible strategy for the prevention and treatment of tissue adhesion, and more broadly, the well‐known implant‐derived inflammatory responses.